Հնչակյան պարբերական մամուլը. սկզբնավորման շրջան - Ռուբեն Խուրշուդյան (ՀՀ ԳԱԱ հրատ.)
Образование армянских политических партий в последние десятилетия XIX века привели к новому явлению в истории армянской печати — появлению партийной печати. The formation of Armenian political parties during the last decade of the 19th century resulted in the emergence of party press - a new phenomenon in the history of Armenian press.
Keywords: General Works; Պարբերական; J Political Science; JPP Political Parties